2014
DOI: 10.1089/thy.2014.0217
|View full text |Cite
|
Sign up to set email alerts
|

Is Malignant Nodule Topography an Additional Risk Factor for Metastatic Disease in Low-Risk Differentiated Thyroid Cancer?

Abstract: Our data show for the first time that a location of a thyroid cancer in the isthmus is an additional risk factor for RAI avid metastatic disease in pT1a-pT1b DTC patients, regardless of the presence or absence of other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…We recently published that the prevalence of lymph-node metastases was significantly higher in patients with low-risk DTC located in the isthmus compared to those located in thyroid lobes. 1 We concluded that the isthmic localization of the malignant thyroid nodule was an independent risk factor in patients with low-risk DTC. In our series of papillary thyroid carcinoma (PTC), patients with isthmus lesion had undergone TRA by 131radioiodine ablative activity (range 1110-3700 MBq; median 2753 MBq) oral administration and their median follow-up was 5 years (range 2-7 years).…”
Section: Braf (V600e) Mutation In Isthmic Malignant Thyroid Nodulesmentioning
confidence: 75%
See 2 more Smart Citations
“…We recently published that the prevalence of lymph-node metastases was significantly higher in patients with low-risk DTC located in the isthmus compared to those located in thyroid lobes. 1 We concluded that the isthmic localization of the malignant thyroid nodule was an independent risk factor in patients with low-risk DTC. In our series of papillary thyroid carcinoma (PTC), patients with isthmus lesion had undergone TRA by 131radioiodine ablative activity (range 1110-3700 MBq; median 2753 MBq) oral administration and their median follow-up was 5 years (range 2-7 years).…”
Section: Braf (V600e) Mutation In Isthmic Malignant Thyroid Nodulesmentioning
confidence: 75%
“…In our series of papillary thyroid carcinoma (PTC), patients with isthmus lesion had undergone TRA by 131radioiodine ablative activity (range 1110-3700 MBq; median 2753 MBq) oral administration and their median follow-up was 5 years (range 2-7 years). 1 All except one patients reached an 'excellent response' status [i.e. undetectable basal and stimulated thyroglobulin (Tg) serum levels (<1 ng/ml); negative neck ultrasound] 3 with the first 131-radioiodine ablative therapy, as appreciated during the first follow-up performed 12 months after TRA.…”
Section: Braf (V600e) Mutation In Isthmic Malignant Thyroid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thyroid cancers are rare, accounting for about 2–5% of all thyroid nodules 2–4 . Diagnostic evaluation of thyroid nodules includes laboratory tests and thyroid ultrasonography (US).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the "minimal extrathyroid spread" in thyroid carcinoma represents the basis of a systematic scientific analysis of biological relevance, including at the same time the tumor size given as pT category (Table 1) (17,26,32). Furthermore, an analysis of tumor localization as prognostic factor is attractive in the near future (33); on this way, the location of thyroid cancer in the isthmus may be considered as an additional risk factor for radioactive iodine (RAI) avid metastatic disease in pT1a-pT1b DTC patients, regardless of the presence or absence of other risk factors (33).…”
mentioning
confidence: 99%